Piezoelectric energy harvesting in graded elastic metastructures using continuous and segmented electrodes - Schimidt, Camila Sanches; de Sousa, Vagner Candido [UNESP]; De Marqui Junior, Carlos (Springer Nature, 2023)
In this work, we investigate piezoelectric energy harvesting from localized vibration modes of a hybrid metamaterial beam. Undamped spring–mass resonators with graded properties are periodically attached to a host beam, which is also completely covered by piezoceramic layers that are employed to harvest electrical energy from mechanical vibrations. The vibration energy trapped over a certain spatial region of a graded metastructure and over a relatively wide frequency range is an opportunity for wideband piezoelectric energy harvesting. The cancelation of electrical output from localized modes, however, has not been discussed in the literature. Therefore, the numerical exercises in this paper explore piezoelectric energy harvesting from localized vibration modes of a graded metastructure considering both continuous and segmented configurations of the electrodes covering the piezoelectric layers. Compared to the continuous electrodes case, configurations with segmented electrodes provide enhanced energy harvesting performance for specific localized modes and also over the entire range of frequencies where localized modes occur.
Keywords: Electrode configuration; Energy harvesting; Graded metamaterial; Piezoelectricity